Financing Analysis and Educational Efficiency - Andika Novriadi Cibro (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this writer is to discuss about. 1) Knowing education financing and, 2) Education efficiency. This type of research is Library Studies research, which in this study will take various expert opinions and analyze from various theories regarding education financing and taxation. The conclusion of this paper is that education financing is an important component to support the smooth running of education and has a major influence on the success of education. Funding for education comes from the state, parents and communities who play a role in meeting the needs of education. Efficiency is an element that must exist in the management and use of funds earmarked for education. In addition to costs, to achieve quality educational productivity, the placement of human resources must also be efficient. Efficient education funding and human resources can create smooth running of every education organization and have great potential in achieving the expected success. The implementation of an efficient educational process is when the utilization of resources such as time, energy and costs is right on target, with optimal graduates and educational productivity. If you pay attention to the implementation of education in Indonesia before it was far from efficient, where the use of all available resources did not produce graduates as expected, many were even unemployed. Therefore, education now must pay attention to the efficiency of education.